Empirical analysis of loan loss provisions manipulation in Chinese banking system - DENG, KE (2017)
The main purpose of this study is to test the loan loss provisions manipulation mechanism and behaviour of Chinese commercial banks during 2011 and 2016. Because the Chinese banking system has played a more significant role in global economy, it is necessary to pay more attentions to Chinese banks’ solvency abilities and ensure the provisions management system is effective. The capital management, earning smoothing and business cycle hypotheses have been tested on the total components of LLPs, however, the corporate governance hypothesis is tested on the discretionary part of LLPs of the publicly listed banks in China. Correlation research design is used for testing the relationship. System GMM estimator is adopted for estimating the correlation between total LLPs and capital management, income smoothing and the business cycle. Moreover, the Random Effects Model is used to examine the mechanism of corporate governance on the management of LLPs. And the empirical results illustrate that the capital management is insignificantly correlated with LLPs where a negative coefficient can be found. This means that the higher the capital ratio is, there will be fewer LLPs manipulation behaviour in Chinese banks. Also, the earnings smoothing is positive significantly correlated with LLPs which suggests there is earnings smoothing mechanism existed in Chinese banks by using the total amount LLPs. In addition, the business cycle is found to share a negative relationship with LLPs which is significant, this finding can suggest that Chinese banks are likely to pro-cyclically manage the LLPs. However, as for the hypothesis of corporate governance, all the variables (board size, risk management committee ratio, audit committee ratio, presence of chief risk officer, independence of risk management committee and independence of audit committee) denote a negative correlation with the discretionary LLPs, while the independence of board has a positive impact on discretionary LLPs.